Evaluation of safety performance of level crossings in Turkey with data envelopment analysis - Yıldız, Kürşat; Kınacı, Harun (Penerbit Universiti Kebangsaan Malaysia, 2021)
Level crossing, also known as railroad and highway crossings, pose a risk to those who use both modes of transport due to collisions that may occur. This risk associated with level crossings is of great importance both in Turkey and in the world. In this study, data envelopment analysis was performed on the accident data occurring on five types of level crossings in Turkey and a measurement of safety performances of level crossings in Turkey was provided. As a result of the analysis, the most efficient three-level crossings were found to be Hilal-Bandırma in Manisa, Samsun-Kalın in Amasya_1, and Samsun-Kalın in Amasya_2. In addition, a linear regression model that serves with the variables which are the components of level crossing and the number of accidents is established. In this model, it is seen that the ratio of independent variables to dependent variables was statistically significant.